Women and Migration : Responses in Art and History - Ali, Grace Aneiza; Arabindan-Kesson, Anna; Nelson, Kalia Brooks; Toscano, Ellyn; Wangechi Mutu; Willis, Deborah (Open Book Publishers; Global Institute for Advanced Study, NYU, 2019)
The essays in this book chart how women$1 (Bs profound and turbulent experiences of migration have been articulated in writing, photography, art and film. As a whole, the volume gives an impression of a wide range of migratory events from women$1 (Bs perspectives, covering the Caribbean Diaspora, refugees and slavery through the various lenses of politics and war, love and family. -----------Contributors: Ellyn Toscano; Anna Arabindan-Kesson; Sandrine Colard; Kathy Engel; Marianne Hirsch; Wangechi Mutu; Karen Finley; Cheryl A. Wall; Sama Alshaibi; Jessica Ingram; Lorie Novak; Debora Spini; Maaza Mengiste; Isolde Brielmaier; Kellie Jones; Jennifer L. Morgan; Bettina L. Love; Editha MEsina; Allana Finley; Treva B. Lindsey; Pamela Newkirk; Vanessa Perez-Rosario; Sirpa Salenius; Arlene Davila; Patricia Cronin; Roshini Kempadoo; Joan Morgan; Sarah K. Khan; Gayatri Gopinath; Kalia Brooks Nelson; Francille Rusan Wilson; Tiffany M. Gill; Paulette Young; Sharon Harley; Cheryl Finley; Grace Aneiza Ali; Alessandra Capodacqua; M. Neelika Jayawardane; Alessandra Di Maio; Misan Sagay; Gunja SenGupta; Imani Uzari. The contributors, which include academics and artists, offer both personal and critical points of view on the artistic and historical repositories of these experiences. Selfies, motherhood, violence and Hollywood all feature in this substantial treasure-trove of women$1 (Bs joy and suffering, disaster and delight, place, memory and identity. This collection appeals to artists and scholars of the humanities, particularly within the social sciences; though there is much to recommend it to creatives seeking inspiration or counsel on the issue of migratory experiences.s
English
Keywords: 20th century; N5300-7418 Visual Arts- History; Women Artists; Migration; Caribbean